O tłumaczeniu czeskiej prozy autobiograficznej. Przypadek Ludvíka Vaculíka - Zarek, Józef (Przekłady Literatur Słowiańskich, 2011)
About translation of the Czech autobiographical prose. The case of Ludvik Vaculik The article comments upon Polish translators attitude to the novel of the Czech prose writer Vaculik, especially Český snář and Jak se dělá chlapec, fragments of which can be found in Polish magazines of 80’s and 90’s in 20th century. The reception of this prose is linked with the formation and interest decline of the Czech opposition’s situation. The article searches for traces of cultural dialogue in translation attempts.